(untitled) (INNOVATIVE ECONOMY, 2024)
Marchenko T.V., Romaniuk A.S. NATIONAL IDENTITY AND INNOVATIVE DEVELOPMENT AS FACTORS OF ECONOMIC SECURITY OF THE COUNTRY Purpose. Study of the impact of national identity and economic innovativeness as factors of the country’s national and international security on international economic relations; defining the main foundations of national identity, which should be taken into account when developing state policy and forming a national geostrategy, as well as clarifying the relationship between national interests and economic growth based on innovation. Methodology of research. The following methods of scientific analysis were used to implement the identified goals and tasks of the research: historical, systemic, structural-functional and value-normative. The historical method made it possible to trace the nature and peculiarities of the formation of the national idea, as well as to determine the prospects for its development in the period of global transformations. The system method made it possible to comprehensively examine the national identity, to identify its main elements and connections. The structural-functional method helped to reveal the role of the functional unity of society united by the worldview and value concepts of the national idea, as well as to characterize the importance of innovative activity and technological development of industrially developed countries. The value-normative method helped reveal the relationship between national values and their impact on economic security and the course of international economic relations. Findings. The impact of national identity and economic innovativeness on international economic relations is determined, their role in ensuring national security and the formation of state policy is established. The analysis of the impact of globalization processes on the nature and content of the country’s national interests is carried out, the role of the geopolitical factor in this context is determined, and the problem of forming a modern Ukrainian geostrategy in the context of the struggle for the realization of national interests and ensuring the country’s national security is considered. It is substantiated that in the modern world, innovations become a determining factor in the dynamic development, transformation and competitiveness of socio-economic systems in the global space. Originality. The influence of national identity and economic innovativeness as factors of the country’s economic security on international economic relations was investigated on an interdisciplinary basis at the intersection of such scientific disciplines as political science, economics, history, cultural studies and the theory of international relations; some aspects of Ukraine’s economic development strategy are defined, emphasizing the importance of international cooperation, integration processes, and national collective strength for solving future post-war challenges. Practical value. Theoretical provisions, conclusions and recommendations are important for the scientific justification of the optimal mechanism for the implementation of the national economic strategy, taking into account the national identity and economic innovativeness in modern social and political conditions, as well as the possibility of applied application of these results in the educational process. Key words: national identity, innovation, innovative activity, national idea, geopolitics, economic security, economic nationalism, international economic relations.